HSP90 Inhibitor Ganetespib Enhances the Sensitivity of Mantle Cell Lymphoma to Bruton’s Tyrosine Kinase Inhibitor Ibrutinib - Lu, Ziwen; Wang, Zhixin; Tu, Zhigang; Liu, Hanqing (Frontiers in Pharmacology, 2022)
Mantle cell lymphoma (MCL) is a highly aggressive and heterogeneous B-cell lymphoma. Though Bruton's tyrosine kinase (BTK) inhibitor ibrutinib has shown great efficacy as a single agent for MCL treatment, the real-world use of ibrutinib is still subject to limitations. Our previous study has shown the treatment with HSP90 inhibitor ganetespib can attack major targets of MCL, luckily complementary to ibrutinib’s targets. In this study, transient ganetespib treatment sensitizes MCL cells to ibrutinib as manifested by the significant decrease of IC50 values, percentages of EdU (5-Ethynyl-2′-deoxyuridine) positive cells, and levels of p-AKT and NF-κB after combinational treatment. Additionally, pretreatment with ganetespib enhanced cell cycle arrest induced by ibrutinib at G0/G1 phase and significantly decreased levels of cell cycle promoting proteins CDK2, 4, and 6. Pretreatment with ganetespib also enhanced cell apoptosis induced by ibrutinib through the upregulation of cleaved-caspase 9 and downregulation of BCL-2 in MCL cells at the molecular level. The sequential administration of ganetespib and ibrutinib had similar effects on increasing DNA damage as the transient treatment with ganetespib as demonstrated by the improved percentage of γH2AX and 53BP1 foci. Furthermore, ganetespib significantly increased inhibition of tumor growth mediated by ibrutinib in vivo, confirmed by the changes of the expression levels of Ki-67 and BCL-2 through immunohistochemistry assays. This study indicates that HSP90 inhibitor ganetespib maybe ideal for the combinational use with BTK inhibitor ibrutinib to target major pathogenesis-associated signaling pathways for MCL treatment which may help identify new possibilities for clinical trials.